A Randomized Trial Comparing Short versus Prolonged Hemostasis with Rescue Recanalization by Ipsilateral Ulnar Artery Compression: Impact on Radial Artery Occlusion—The RESCUE-RAO Trial - Dmitrii V. Ognerubov; Alexander Sedaghat; Sergey I. Provatorov; Andrey S. Tereshchenko; Olivier F. Bertrand; Ivo Bernat; Goar K. Arutyunyan; Olga A. Pogorelova; Maria I. Tripoten; Tatyana V Balakhonova.; Anatoliy N. Samko; Evgeny V. Merkulov (Journal of Interventional Cardiology)
Background. Despite the enormous benefits of radial access, this route is associated with a risk of radial artery occlusion (RAO). Objective. We compared the incidence of RAO in patients undergoing transradial coronary angiography and intervention after short versus prolonged hemostasis protocol. Also we assessed the efficacy of rescue 1-hour ipsilateral ulnar artery compression if RAO was observed after hemostasis. Material and Methods. Patients referred for elective transradial coronary procedures were eligible. After 6 F radial sheath removal, patients were randomized to short (3 hours) (n = 495) or prolonged (8 hours) (n = 503) hemostasis and a simple bandage was placed over the puncture site. After hemostasis was completed, oximetry plethysmography was used to assess the patency of the radial artery. Results. One thousand patients were randomized. Baseline characteristics were similar between both groups with average age 61.4 ± 9.4 years (71% male) and PCI performed on half of the patients. The RAO rate immediately after hemostasis was 3.2% in the short hemostasis group and 10.1% in the prolonged group (p<0.001). Rescue recanalization was successful only in the short group in 56.2% (11/19); at hospital discharge, RAO rates were 1.4% in the short group and 10.1% in the prolonged group (p<0.001). Conclusion. Shorter hemostasis was associated with significantly less RAO compared to prolonged hemostasis. Rescue radial artery recanalization was effective in > 50%, but only in the short hemostasis group.